Mechanisms of oral ciprofloxacin-induced depressive-like behavior and the potential benefit of lactulose: A correlation analysis - Havizur Rahman; Kusnandar Anggadiredja; Lucy Sasongko (Toxicology Reports)
Prolonged administration of antibiotics may be associated with depression due to the potential risk of dysbiosis. Thus, the restoration of microbial balance, through administration of prebiotics, might overcome the problem. This study investigated the mechanisms of antibiotic-induced depression, which were explored through statistical correlation analysis. The potential benefit of lactulose, a prebiotic, on this behavioral disorder was further assessed. The rats were assigned to groups receiving 102.8 mg/kg ciprofloxacin daily for 1, 8, 15, or 22 days. A different group of rat was given the same regimen for 8 days accompanied with lactulose at 2056 mg/kg. Upon completion of ciprofloxacin administration, the rats were tested for depression-like behavior (forced swimming test, FST; and sucrose preference test, SPT). They were then sacrificed for biochemical assessment in the hippocampus and prefrontal cortex. The mechanism studies revealed significant correlation between SPT vs. serotonin in the hippocampus, and SPT vs. serotonin, cortisol, NF-κB in the prefrontal cortex. Meanwhile, FST was significantly correlated with serotonin in the hippocampus and the prefrontal cortex, while in the prefrontal cortex it was significantly correlated with cortisol, NF-κB, and IL-6. Based on the afore-mentioned results, it was found that lactulose improved FST by targeting serotonin in the hippocampus. This study indicate that ciprofloxacin induce depression-like behavior via modulation of several neurotransmitter system as well as proinflammatory cytokines in the hippocampus and prefrontal cortex. The results further suggest the potential of lactulose to improve this behavior.